The Effect of Disciplinary Measures on the Learning Motivation of Students at Pondok Modern Al-Amanah Baubau - Fiqi Hidayat Atmir (Jurnal Pendidikan Agama Islam Indonesia (JPAII), 2026)
Purpose of the study: To analyze and describe the impact of sanctions and discipline on the learning motivation of students at Pondok Modern Al Amanah. Methodology: This study employs a quantitative approach using an associative research design. The research design utilized is multiple linear regression. The population for this study consists of 200 participants, and the sample size is 30% of the population, resulting in 30% × 200 = 60 students. Data collection methods used in this study include questionnaires, documentation, and interviews. Data analysis includes testing classical assumptions, descriptive statistics, and hypothesis testing. Main Findings: The F-test indicates that sanctions and discipline, when considered together, significantly influence learning motivation, with an F-value of 46.501 and a significance level of 0.001 (< 0.05). This implies that the regression model is statistically reliable and suitable for explaining the combined effect of sanctions (X1) and discipline (X2) on learning motivation (Y) at the Al-Amanah Modern Islamic Boarding School. The combined R² value of 0.620 indicates that 62% of the variation in students’ learning motivation can be explained jointly by sanctions and discipline, while the remaining 38% is attributed to other factors outside the model. Novelty/Originality of this study: The imposition of sanctions that are fair, proportionate, and educational in nature has been shown to increase students’ awareness and sense of responsibility toward the learning process.